Mortality management and climate action: A review and reference for using Terror Management Theory methods in interdisciplinary environmental research - Smith, Lauren K. M.; Ross, Hanna C.; Shouldice, Stephanie A.; Wolfe, Sarah Elizabeth (Wiley, 2022)
Global climate change awareness is increasing, but efforts to convey information can trigger undesirable behaviors, including denial, scepticism, and increased resource consumption. It is therefore essential to more fully investigate social-psychological responses to climate information and messaging if we are to prompt, support, and sustain pro-environmental behaviors. Yet consideration of these responses is typically absent from interdisciplinary environmental study designs. Of specific relevance is research using social psychology’s Terror Management Theory (TMT) showing that people’s efforts to repress mortality salience or awareness significantly influence their attitudes, beliefs, and behaviors. Research on mortality salience’s influence on climate change beliefs is progressing, but to date a systematic scoping review of the literature has been unavailable. Here, we provide such a review. We propose that TMT insights and methods must be better integrated into research designs to guide climate communications and to generate the comprehensive cultural and behavioral changes needed to address societies’ climate problems. We introduce a methodological framework for interdisciplinary researchers to incorporate TMT into their research designs and help practitioners anticipate how their mortality-laden messaging could trigger unintentional social-psychological responses that degrade climate communication strategies.
This is the peer reviewed version of the following article: Smith, L. K., Ross, H. C., Shouldice, S. A., & Wolfe, S. E. (2022). Mortality Management and climate action: A review and reference for using Terror Management Theory Methods in interdisciplinary environmental research. WIREs Climate Change, 13(4), which has been published in final form at https://doi.org/10.1002/wcc.776. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.
Keywords: climate change; emotion; pro-environmental behavior; mortality awareness; research methods; sustainability; terror management theory